Analisis pengembangan Agroindustri Pindang Family dengan Pendekatan Triple Layered Business Model Canvas - Fitra Ramadhani Setiawan; Illia Seldon Magfiroh (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2023)
The pindang family agroindustry is a pindang fish agroindustry that produces pindang fish with tuna as the main raw material, which is intended to get more added value and a more durable product. This study aims to (1) determine the mapping of the TLBMC business model of the Pindang Family Agroindustry, (2) obtain decision making using PMIA in the Pindang Family Agroindustry business model. the research method used in this research is descriptive analytic. The sampling method used is purposive sampling. The results of this research are (1) Pindang Family Agroindustry can describe all the elements in the economic and environmental layers, that is, it can describe the nine elements, in the social layer it can only describe five elements and four elements cannot be described. (2) The results of decision making using PMIA show that the Pindang Family Agroindustry is said to be sustainable because the final score is positive, which is equal to 282, consisting of 107 economic layer scores, 104 environmental layer scores, and 71 social element scores.